The Digital Literacy On Constructivist Philosophical Aspect - Imma Rachayu; Siti Masitoh; Mochmad Nursalim (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
Indonesia is the third in Asia with internet users reaching 212.35 million people in March 2021 according to internetworldstats data. After the Covid-19 pandemic, there were changes in habits that appeared because they had never happened, thus triggering the community to find the right solution in overcoming changes in both activities and habits. The platforms that are often accessed are social whatsapp, facebook, youtube, Instagram, tiktok, telegram, twitter and line with the age range that often accesses is the age of 13 to 18 years. Internet access in the form of social media platforms has not been able to balance their ability to use digital media to develop their potential in the form of critical thinking patterns and build logic. Digital literacy in constructivist philosophical aspects uses literature research methods from several relevant sources. The purpose of this article is to describe the addition of knowledge and a constructivist learning process through digital literacy. The results of this literature study showed that when constructivist philosophical aspects were formed in individuals, they would build critical thinking patterns in processing information in the form of symbols and writing.